If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5y = -8 Solving 6x + -5y = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5y' to each side of the equation. 6x + -5y + 5y = -8 + 5y Combine like terms: -5y + 5y = 0 6x + 0 = -8 + 5y 6x = -8 + 5y Divide each side by '6'. x = -1.333333333 + 0.8333333333y Simplifying x = -1.333333333 + 0.8333333333y
| 3y+20=6y+30 | | 3y+10=6y+30 | | 10y=2y+5+7y | | 6*4-5*8+(21)= | | 3x-5=9x+9 | | -24.6-m=18.4 | | 3y+20+3y+10=90 | | 3y+20=3y+10 | | 46-8x=8x+18 | | x=10-4(2) | | -(3y+3)-(-2y-4)=-8 | | 0.25x+.05(14-x)=.10(-9) | | 2r+7=-1 | | N+4=3.6 | | 4x^2-19x+16=4x+1 | | -4x-7x+2x=36 | | -9(x-3)+7x=-2(x+2)+7 | | -37=3x+11+7x | | 2x+8=2x | | 6y=108 | | -9(x-3)+7x=2(x+2)+7 | | 6x^2-11x-2=0 | | 7+3x=19x+x | | c-2=0 | | x^4-26x^2+160=0 | | 8y+2=10+7y | | 4p+5+7p=-1 | | 1a+2b+1c=58 | | -6(k+4)=30(k-2) | | x-4x=5 | | 10(x-4)(2x+9)=0 | | -27=8x+5x |